Scarcity promotion triggers impulse buying behaviour / Dr. Syahida Abd Aziz and Dr. Roziyana Jafri - Abd Aziz, Syahida; Jafri, Roziyana (Universiti Teknologi MARA, Kedah, 2024)
Impulse purchasing among young and adult consumers is showing a rising trend. It is not uncommon for people to purchase items they may not necessarily need. This is because they do not want to feel left out or to miss the items once those items are sold out. Such purchasing behaviour can lead to overspending and financial difficulties. Thus, it is crucial to be aware of these emotions and restrict one’s purchasing to necessities to be consistent with one’s budget and personal values. However, the scarcity promotion strategy employed by marketers has worsened the situation by driving consumers to purchase the items they perceive as being in limited supply. Hence, the influence of scarcity promotion on impulse buying, the drawbacks of impulse buying, and how to reduce the tendency of impulse buying driven by scarcity promotion are discussed in this paper.